Experimental study of the coherent vorticity in slightly under-expanded supersonic screeching jets. Issue 2 (April 2019) - Mercier, Bertrand; Castelain, Thomas; Bailly, Christophe
The noise generation mechanism of screech tone by shock leakage in underexpended round jets is experimentally investigated by means of phase-averaged velocity fields. Two jet flows at Mach numbers 1.10 and 1.15 are measured by a particle image velocimetry apparatus simultaneously with their near acoustic fields and sorted according to their phase with respect to a screech period. The coherent vorticity fields are then computed and analyzed. They depict two distinct regions of high level of vorticity fluctuations. Thanks to the knowledge about shock leakage gathered in previous studies, the role of both regions in the acoustic generation process is identified and a region of the flow is recognized as suitable for emitting acoustic waves. Phase-averaged schlieren visualizations are also computed and used to determine the motion of the first five shocks over a screech period. For both jets, the peak shock motion is found at the fourth shock tip. This shock is also located in the region recognized as favorable for the shock leakage to be observed.